The management of blood and body fluids in a Kenyan university hospital : a nursing perspective - Ngesa, Anna Adhiambo (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MCur (Nursing Science))--University of Stellenbosch, 2008.